2020
DOI: 10.3389/fphar.2020.00373
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Dehydrogenase 2 Protects Against Post-Cardiac Arrest Myocardial Dysfunction Through a Novel Mechanism of Suppressing Mitochondrial Reactive Oxygen Species Production

Abstract: production. Through metabolizing 4-HNE, ALDH2 significantly inhibited mitochondrial ROS production. Our findings provide compelling evidence of the cardioprotective effects of ALDH2 and therapeutic targeting this enzyme would provide an important approach for treating post-cardiac arrest myocardial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 50 publications
4
20
0
Order By: Relevance
“…To understand the effect of ALDH2 activation on HS, Alda-1 was pretreated in HS induced HUVECs. Consistent with previous studies (29,31,48), Alda-1 (20mM) significantly augmented ALDH2 activity (Figure 3A) and reduced heat stress-induced ROS accumulation (Figures 3B, C). Alda-1 ameliorated the heat stress-induced cell death (Figure 3D) and reduced heat stressinduced apoptosis (Figure 3E) and senescence (Figure 3F) in HUVECs.…”
Section: Alda-1 Attenuates Heat Stress-induced Activation Of Inflammatory Pathways and Preserved Viability In Huvecs In Vitrosupporting
confidence: 92%
“…To understand the effect of ALDH2 activation on HS, Alda-1 was pretreated in HS induced HUVECs. Consistent with previous studies (29,31,48), Alda-1 (20mM) significantly augmented ALDH2 activity (Figure 3A) and reduced heat stress-induced ROS accumulation (Figures 3B, C). Alda-1 ameliorated the heat stress-induced cell death (Figure 3D) and reduced heat stressinduced apoptosis (Figure 3E) and senescence (Figure 3F) in HUVECs.…”
Section: Alda-1 Attenuates Heat Stress-induced Activation Of Inflammatory Pathways and Preserved Viability In Huvecs In Vitrosupporting
confidence: 92%
“…ALDH2 can transform β-aminopropion-aldehyde to β-alanine [ 30 ] and is widely studied as an important cardioprotective factor [ 31 ]. Activate ALDH2 promote mitochondrial homeostasis and suppress mitochondrial ROS (reactive oxygen species) [ 32 , 33 ]. In our results, both MLYCD and ALDH2 was obviously up-regulated that MLYCD may a marker of ROS in central precocious puberty and ALDH2 may play an endogenous protective role.…”
Section: Discussionmentioning
confidence: 99%
“…The prototype of the ALDH2 activator, Alda-1, activated the wild type enzyme and restored the activity of the ALDH2*2 mutant enzyme by acting as a structural chaperone [29]. In a recent study, the activation of ALDH2 prevented the cardiac-arrest-induced death of cardiomyocytes from 4-HNE-induced mitochondrial ROS production and the subsequent mitochondrial damage and cell apoptosis [30]. In this study, we demonstrated that Alda-1 ameliorated 4-HNE-induced beta cell death, apoptosis, and mitochondrial, as well as cytoplasmic ROS levels.…”
Section: Discussionmentioning
confidence: 99%